2017
DOI: 10.1007/s00586-017-5153-0
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of clinical tests to assess the anatomical integrity of the cervical spine in adults with neck pain and its associated disorders: Part 1—A systematic review from the Cervical Assessment and Diagnosis Research Evaluation (CADRE) Collaboration

Abstract: Little evidence exists to support the use of clinical tests to evaluate the anatomical integrity of the cervical spine in adults with neck pain and its associated disorders. We found preliminary evidence to support the use of the extension-rotation test, neurological examination, Spurling's and the upper limb neurodynamic tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
0
22
1
3
Order By: Relevance
“…Although there is only limited evidence for clinical tests, even less is known about the diagnostic accuracy of the patient interview to diagnose cervical radiculopathy. A recent systematic review [13] on the diagnostic accuracy of interview items for cervical radiculopathy could only include two studies [14,15]. The authors concluded that shoulder or scapular pain, and a decrease of symptoms with neck movements are the patient interview items that are most indicative of cervical radiculopathy [13].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although there is only limited evidence for clinical tests, even less is known about the diagnostic accuracy of the patient interview to diagnose cervical radiculopathy. A recent systematic review [13] on the diagnostic accuracy of interview items for cervical radiculopathy could only include two studies [14,15]. The authors concluded that shoulder or scapular pain, and a decrease of symptoms with neck movements are the patient interview items that are most indicative of cervical radiculopathy [13].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review [13] on the diagnostic accuracy of interview items for cervical radiculopathy could only include two studies [14,15]. The authors concluded that shoulder or scapular pain, and a decrease of symptoms with neck movements are the patient interview items that are most indicative of cervical radiculopathy [13]. They reported high specificity values for neck pain, arm pain, pain that is constant over time and sensory loss [13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations